Potential value of hepatic lipids from white sea bream (Diplodus sargus, L.) as a good source of biomedical components : seasonal variations - Varljen, Neven (Array, 2009)
Summary: The aim of this study is to evaluate the potential value of hepatic lipids of the white sea bream, Diplodus sargus, as a source of important biomedical components. Fatty acid compositions of hepatic neutral (triacylglycerols) and polar (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) lipid fractions were determined. In order to verify the influence of a season on the fatty acid compositions of liver lipid fractions, fish were captured and analyzed in winter, spring, summer and autumn. Eighteen different fatty acids were identified in the analyzed lipid fractions. The major constituents of total fatty acids were saturates: palmitic (16:0) and stearic acid (18:0), monounsaturated fatty acids: oleic (18:1 n-9) and palmitoleic acid (16:1 n-7), while arachidonic acid (20:4 n-6), eicosapentaenoic (20:5 n-3) and docosahexaenoic acid (22:6 n-3) were the major constituents among polyunsaturated fatty acids. Their amounts and ratios differed significantly among seasons in different lipid fractions. Total unsaturated fatty acids in all analyzed lipid fractions were the highest in the winter period. Saturated fatty acids were the highest in the spring period in all lipid fractions. Eicosapentaenoic and docosahexaenoic acid achieved the highest values in triacylglycerols in the winter period. Unsaturation indices and n-3/n-6 values were also influenced by the season. This study revealed a seasonality pattern of D. sargus hepatic fatty acid composition